Deskripsi Kemampuan Representasi Matematis Siswa Kelas VIII SMP/MTs Ditinjau Dari Gaya Kognitif Visualizer Dan Verbalizer - La Eru Ugi; Afudin La Arua; Shindy Ekawati (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2023)
Mathematical representation ability is one of the basic abilities that every student must have in examining, expressing, and exploring a mathematical idea in the form of a problem, information, definition, etc. to find an appropriate solution according to the results of the representation, whether in the form of pictures, words, tables, symbols, graphs, and patterns in mathematics. The biggest reason that hinders students' bright ideas from appearing is the weak ability of students' mathematical representations which hinders students in determining the completion of mathematical problems and even less careful in reading story problems, weak in problem analysis, inaccurate, and difficulty connecting between concepts. The subjects of this study were students of grade VIII in one of the MTs in the Angkona sub-district, which consisted of two students. The instrument used for this research is the Visualizer Verbalizer Questionnaire (VVQ). Mathematical representation ability test questions and interviews. This study used descriptive qualitative method. Based on the data analysis, it can be concluded that the students' representation abilities with the visualizer and verbalizer styles are quite good. There are several interesting things from the two research subjects, namely the Visualizer subject (SVi) in solving a problem prioritizing the visual aspect in examining each question and the information contained in the a simpler form in representing an image and illustration of a flat shape. Meanwhile, the subject verbalizer (SVe) is more likely to explore detailed and clear information in representing something related to the Pythagorean theorem.